2022
DOI: 10.1109/tnsre.2022.3175464
|View full text |Cite
|
Sign up to set email alerts
|

OGSSL: A Semi-Supervised Classification Model Coupled With Optimal Graph Learning for EEG Emotion Recognition

Abstract: Electroencephalogram (EEG) signals are generated from central nervous system which are difficult to disguise, leading to its popularity in emotion recognition. Recently, semisupervised learning exhibits promising emotion recognition performance by involving unlabeled EEG data into model training. However, if we first build a graph to characterize the sample similarities and then perform label propagation on this graph, these two steps cannot well collaborate with each other. In this paper, we propose an Optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…5.4.5. Limited SSL Some recent EEG-SSL [25][26][27] methods are specifically proposed to label the unlabeled EEG segments that are available in the training phase. Thus, the classification results show the quality of generated pseudo-labels for the unsupervised set.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5.4.5. Limited SSL Some recent EEG-SSL [25][26][27] methods are specifically proposed to label the unlabeled EEG segments that are available in the training phase. Thus, the classification results show the quality of generated pseudo-labels for the unsupervised set.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the classification results show the quality of generated pseudo-labels for the unsupervised set. In this experiment, we compare the proposed method with OGSSL 1 [27] in this setting on the DEAP dataset for both valence and arousal recognition tasks, and the SEED dataset while the number of labeled data is limited (num labeled 200, 1000 { } Î…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, most studies utilize EEG as the main source for biometric construction due to the convenience of signal acquisition [ 19 , 20 , 21 , 22 , 23 , 24 ]. However, a major problem with EEG is its low SNR because the brain’s electrical signals decay significantly while passing through the skull and scalp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the keys generated by behavioral biometrics are generally very short, e.g., approximately 40 bits [ 16 ], which may be insufficient security for applications with high security requirements. Recent studies have demonstrated that the human brain can provide superior revocable biometric features [ 19 , 20 , 21 , 22 , 23 , 24 ]. Brain waves are continuous physiological signals with variable characteristics that change in real time; thus, it is extremely difficult to steal or imitate brain signals.…”
Section: Introductionmentioning
confidence: 99%